One-pot growth of triangular SnS nanopyramids for photoacoustic imaging and photothermal ablation of tumors. (6th August 2019) - Yang, Dongliang; Chen, Fei; He, Shili; Shen, Haifeng; Hu, Yanling; Feng, Ning; Wang, Siyu; Weng, Lixing; Luo, Zhimin; Wang, Lianhui
Abstract : Triangular SnS nanopyramids act as an efficient theranostic nanoagent for photoacoustic imaging and photothermal therapy. Abstract : Recently, metal sulfides have received great attention in biomedical applications due to their fascinating properties. Herein, poly(vinylpyrollidone)-modified triangular SnS nanopyramids were synthesized via a simple one-pot hydrothermal process. The as-prepared SnS nanopyramids exhibit low toxicity, and a high extinction coefficient (14.25 L g −1 cm −1 ) and photothermal conversion efficiency (35.4%), enabling effective eradication of tumors in mice. Furthermore, photoacoustic imaging experiments suggest that SnS nanopyramids can be used for tumor photoacoustic imaging. These results indicate that SnS nanopyramids can serve as a nanoplatform for photoacoustic imaging and photothermal therapy in biomedical applications.